RESEARCH OF THE OPERATION PRINCIPLE OF OF THE MULTIPLEXER AND DEMULTIPLEXER USING MODERN PEDAGOGICAL TRAINING TECHNOLOGIES - Kinzhebayeva , D.A.; Kinzhebayeva, Kinzhebayeva A.S. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
This article presents a methodological technology for studying digital logic devices. Recommendations on the technology of teaching digital logic devices using rational, best methodological methods and teaching techniques are given. The proposed topic is "Multiplexer and demultiplexer". Studying methods used: modular studying, developmental studying, demonstration (frontal), step-by-step studying, problem-based studying. The process of implementing learning technology explained by the plan prepared for the lesson (mostly the basics of electronics in Kazakhstan are not included into the educational basis of the school and are only taught in higher educational institutions, therefore, the basic learning range, conventionally referred to in the lesson plan, seminars or lectures.